Effects of isoquinoline alkaloids from Macleaya cordata on growth performance, survival, immune response, and resistance to Vibrio parahaemolyticus infection of Pacific white shrimp (Litopenaeus vannamei). - Pavarist Bussabong (Public Library of Science (PLoS), 2021)
Isoquinoline alkaloids (IQs) from Macleaya cordata are promising natural products for enhancing the growth performance and overall health condition of farmed animals. The present study aimed to investigate the effects of two formulas of IQ extract, provided in either a powdered formula (IQ-E) or a water-soluble, granulated formula (IQ-WS) and containing the main active component sanguinarine at a concentration of 0.5% and 1%, respectively, on the growth, survival, immune response, and resistance to Vibrio parahaemolyticus infection of Pacific white shrimp (Litopenaeus vannamei). In Experiment 1, the postlarvae were divided into five groups (four replicates/group and 100 shrimp/tank) and fed four times/day for 30 days with a control feed, IQ-E at 200 or 300 mg/kg of feed, or IQ-WS at 100 or 150 mg/kg of feed. In Experiment 2, the surviving shrimp from Experiment 1 were redistributed into six groups (four treatment groups as in Experiment 1 plus the positive and negative controls with four replicates/group and 30 shrimp/tank) and challenged with V. parahaemolyticus by immersion at a concentration of 103 colony-forming units (CFU)/mL and were fed with the same diets for another 14 days. The results revealed that all IQ-fed shrimp in Experiment 1 had significantly enhanced survival rates and immune parameters (total hemocyte count and phagocytic, phenoloxidase, and superoxide dismutase activities) compared to the control group, even though the growth performances were similar across all groups. In Experiment 2, all IQ-fed groups showed better growth performance and survival rates compared to the positive control. Other than in the positive control group, no histopathological lesions in the hepatopancreas and the intestine were found. In summary, the current study demonstrated the benefits of using IQs from M. cordata as feed additives for improving the growth performance, survival rate, immune responses, and resistance to vibriosis of Pacific white shrimp.